Pokazateli udarnogo obyoma krovi u yunoshej, zanimayushchikhsya fizicheskimi uprazhneniyami dinamicheskogo i staticheskogo kharaktera - Abzalov, R. A.; Vakhitov, I. Kh.; Safin, R. S.; Kabysh, E. G. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The influence of static kinds of physical exercises on young men' pump function of heart has the features to which study the present research is devoted. Authors have analyzed parameters of pump function of heart in young skiers and bodybuilders by the method of thetrapolar arteriography. The flexible tape electrodes, which strengthened with the rubber bandage, were used for the registration of arteriogramm. The increase of WCV occurs depending on use of physical exercises of dynamic or static character in training process. The bodybuilders have the statistically higher parameters of cardiac output, than the persons who are not engaged in sports. It is probably caused by the hypertrophy of a myocardium, developing during occupations by static physical exercises. However, the more expressed increase of WCV is promoted by the exercises of dynamic character, which are applied in training of skiers-racers.